A binder-free Ni2P2O7/Co2P2O7 nanograss array as an efficient cathode for supercapacitors. (22nd July 2020) - Matheswaran, Priyadharshini; Karuppiah, Pandi; Chen, Shen-Ming; Thangavelu, Pazhanivel
Abstract : Binder-free Ni2 P2 O7 /Co2 P2 O7 cathode of nanograss morphology, delivered an energy and power density of 33.2 W h kg −1 and 257.8 W kg −1 respectively. Through power law, the contribution of each type of mechanism in charge storage process was calculated. Abstract : Building a novel electrode with improved electrochemical behaviour has great scope in the area of supercapacitors. In this work, binder-free 1D nanograsses of Ni2 P2 O7 /Co2 P2 O7 nanocomposites were grown on nickel foam through a simple hydrothermal method at different processing temperatures. A precise examination was carried out to study the influence of the processing temperature on the morphology and electrochemical attributes. Ex situ morphological pictures confirmed the reliance of structure on the hydrothermal temperature and the obtained one-dimensional morphology encouraged ion interaction through short channels. The patterned nanograsses were grown at 140 °C with uniform interspacing and exhibited better electrochemical performance due to short, diffusive 1D pathways. Using the power law, the capacitive parts of the total capacitance were elucidated. The better electrochemical performance from charge–discharge indicates that the binder-free NiP2 O7 /CoP2 O7 1D nanograsses would be an appropriate cathode for an efficient hybrid capacitor. The optimized electrode as the cathode in the device showed better energy density and long-lasting cycle life (80% capacity retention after 2000 cycles). Our outcomes indicate that the Ni2 P2 O7 /Co2 P2 O7 1D nanograss pattern has good potential for use as a cathode for hybrid supercapacitors.